Angel time : a novel - Rice, Anne, 1941- (New York : Anchor Books, 2010)
Contract killer Toby O'Dare accepts a seraph's offer to leave his violent existence in order to save lives, and finds himself transported to thirteenth-century England and challenged to defend falsely accused Jewish citizens.
Originally published: New York : Alfred A. Knopf, 2009.
Keywords: Angels -- Fiction; Assassins -- Fiction; Suspense fiction